2006
DOI: 10.1097/01.hjh.0000199800.72563.26
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions to reduce raised blood pressure: a systematic review of randomized controlled trials

Abstract: Patients with elevated blood pressure should follow a weight-reducing diet, take regular exercise, and restrict alcohol and salt intake. Available evidence does not support relaxation therapies, calcium, magnesium or potassium supplements to reduce blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
398
2
56

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 662 publications
(469 citation statements)
references
References 149 publications
(140 reference statements)
13
398
2
56
Order By: Relevance
“…Interventions targeted to populations with blood pressure above goal will therefore become less effective in lowering CVD incidence as blood pressure awareness, treatment, and control continue to improve, limiting the target population 40. Conversely, population‐wide lifestyle approaches to blood pressure reduction, as encouraged by the 2013 AHA/ACC Guideline on Lifestyle Management to Reduce Cardiovascular Risk, have been successful in reducing CVD across a wide range of blood pressures 15, 16, 44. For example, prior population‐wide intervention studies of salt reduction demonstrated decreases in morbidity, mortality, and healthcare costs with as little as 1 g less of salt per day (equivalent to 1/6 of a teaspoon)15 and are feasible, as evidenced by recent dietary salt reduction programs in the United Kingdom focused on manufactured food that decreased mean sodium content in the food supply by 7% 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions targeted to populations with blood pressure above goal will therefore become less effective in lowering CVD incidence as blood pressure awareness, treatment, and control continue to improve, limiting the target population 40. Conversely, population‐wide lifestyle approaches to blood pressure reduction, as encouraged by the 2013 AHA/ACC Guideline on Lifestyle Management to Reduce Cardiovascular Risk, have been successful in reducing CVD across a wide range of blood pressures 15, 16, 44. For example, prior population‐wide intervention studies of salt reduction demonstrated decreases in morbidity, mortality, and healthcare costs with as little as 1 g less of salt per day (equivalent to 1/6 of a teaspoon)15 and are feasible, as evidenced by recent dietary salt reduction programs in the United Kingdom focused on manufactured food that decreased mean sodium content in the food supply by 7% 13.…”
Section: Discussionmentioning
confidence: 99%
“…These models provided estimates of the IRDs for CHD, stroke, or HF associated with a 1 mm Hg decrement in SBP at study baseline potentially achievable after lifestyle interventions were fully implemented16, 17, 33, 34, 35; estimates for a 2‐mm Hg reduction were obtained by multiplying the SBP regression coefficient by 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Lifestyle interventions as improved diet, physical exercise, salt and alcohol restriction have been shown to reduce SBP by 2-5 mm Hg. 3 FM as functional food might be a useful lifestyle intervention and deserves careful consideration.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most exercise trials comprised three to five supervised sessions of 30-60 min of aerobic exercise. 4 Although exercise reduced blood pressure to a greater extent in patients with elevated blood pressure level at baseline, exercise also lowered blood pressure in individuals who had normal baseline levels. 5 In accordance with these data, a public health perspective for the primary prevention of hypertension recommends regularly engaging in aerobic physical activity such as brisk walking, jogging or cycling for at least 30 min on most days of the week.…”
mentioning
confidence: 99%